(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Mineralogical composition of three surface soils from Urir Char ? an environmentally vulnerable small offshore island of Bangladesh ? was determined by X-ray diffraction analysis. In the bulk soils layer silicates and quartz were the dominant minerals while the quantity of feldspars was around ten percent. Quantity of weatherable minerals was very high in the soils. Illite was the dominant mineral in the clay fraction of the soils. The second dominant clay mineral was smectite which comprised around one-fourth of the clay fraction closely followed by chlorite with a small quantity of kaolinite mineral. Soil vermiculite and mixed layer minerals were absent in these soils. These soils had a mixed mineralogical composition with a high cation exchange capacity and percent base saturation. Texturally the soils were silty loam. Exchangeable Ca++/ Mg++ ratio was less than unity. Magnesium solonization was considered as the dominant pedogenic process along with gleization. There was problem of salinity as the elevation of land was around one meter above the mean sea level. Natural calamities like tropical cyclones and tidal surges were highly devastating as the island was completely washed with sea water. J. Asiat. Soc. Bangladesh, Sci. 39(1): 95-104, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16038